An Annotated Translation of Burnets’s a Little Princess from English into Indonesian - Dingga Nur Ilmi Ma’rifah (UPT P2M Politeknik Negeri Malang, 2023)
Annotated translation research is type of research which describes the translation process of a document with the problem along with its solutions by giving some notes. The object of this research is a book titled “A Little Princess” by Frances Hodgson Burnett, which translated by the researcher. This research aims to: 1. elaborate on the researcher’s difficulties during translating the novel, 2. find out the strategies which are used by the researcher to solve the problem. The researcher uses introspective and retrospective methods in this research. There were twenty sixth of difficulties found. All the difficulties found consisted of twelve words, eleven phrases, and four clauses. All the problems then were solved by employing both semantic and pragmatic strategies. The researcher only takes ten strategies namely; information change, paraphrase strategy, abstraction changes, distribution change, emphasis change, semantic changes, synonymy, explicitness change, hyponymy strategy. These research findings were beneficial especially for novel translators and the students of D3 Program in Applied English in State Polytechnic of Malang. The findings were used to give the solutions of problems during translation process.